2007
DOI: 10.1007/s00595-006-3388-1
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Adenoma with Extensive Extracellular Mucin Deposition: Report of a Case

Abstract: A thyroid tumor with extensive extracellular mucin deposition is extremely rare. We herein describe a case of a thyroid adenoma with prominent myxoid stroma. A 63-year-old man presented with a mass in his right anterior neck. Radiological examinations showed this mass to be a thyroid tumor with a cystic component. The histopathological findings showed the stroma of this tumor to consist of abundant myxoid materials which stained gray-bluish for hematoxylin-eosin. The myxoid material was positive for alcian blu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…The case reports of mucinous thyroid tumors [8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27], including the current three cases, are summarized in table 2. The list does not include the mucin-negative signet ring thyroid tumors described by Schröder and Böcker [28] and commented on by LiVolsi [29].…”
Section: Discussionmentioning
confidence: 99%
“…The case reports of mucinous thyroid tumors [8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27], including the current three cases, are summarized in table 2. The list does not include the mucin-negative signet ring thyroid tumors described by Schröder and Böcker [28] and commented on by LiVolsi [29].…”
Section: Discussionmentioning
confidence: 99%
“…24 Mucin can be seen in a wide spectrum of primary thyroid tumors including follicular neoplasms, medullary carcinoma, poorly differentiated carcinoma, papillary and undifferentiated carcinomas, and mucoepidermoid and primary mucinous carcinomas. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]19,25,26 A mucincontaining thyroglossal duct cyst in the thyroid has also been described in the literature. 27 Most of the mucin of these tumors are of intracellular location and a large amount of mucin can cause a signet-ring appearance in signet-ring cell adenoma of the thyroid gland.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Several cases of stromal mucin-producing thyroid neoplasms have also been reported. [8][9][10][11][12][13][14][15][16] We report here on two additional cases of follicular adenoma with thick capsule and extensive stromal mucin deposits. Importantly, this is the first time that BRAF gene mutation analysis is performed in these types of lesions.…”
Section: Introductionmentioning
confidence: 99%
“…They also stated that immunohistochemical staining for thyroglobulin is a useful marker in discriminating signet ring cell adenomas from metastatic signet ring cell carcinomas [6] . Murakami et al [7] reported an unusual case of thyroid adenoma with extensive mucin deposition in the extracellular space. This unusual finding is also termed extensive myxoid stroma, and is thought to be associated with differentiation of thyroid follicular cells into mucin-producing cells [7] .…”
Section: Discussionmentioning
confidence: 99%
“…Murakami et al [7] reported an unusual case of thyroid adenoma with extensive mucin deposition in the extracellular space. This unusual finding is also termed extensive myxoid stroma, and is thought to be associated with differentiation of thyroid follicular cells into mucin-producing cells [7] . Patients with neck masses may present with symptoms including dysphagia, dyspnea, and chronic neck pain.…”
Section: Discussionmentioning
confidence: 99%